Global, regional, and national burden of acute hepatitis (1990–2021): a systematic analysis of the global burden of disease in 2021 - Bai, Zhixun; Chen, Yanjin; Chen, Jiaxi; Pang, Wenyi; Zheng, Rubin; Deng, Miao; Sun, Rui; Lan, Yongping; Li, Houze (Frontiers in Medicine, 2025)
BackgroundAcute viral hepatitis (AVH) remains a global health concern, with significant variations in incidence, mortality, and DALYs across different regions, age groups, genders, and socioeconomic levels. This study explores AVH trends using data from the Global Burden of Disease (GBD) database (1990–2021).MethodsWe analyzed age-standardized incidence, mortality, and DALY rates across 204 countries and 27 super-regions. Trends were quantified using the estimated annual percentage change (EAPC) and decomposition analysis to assess the contributions of population growth, aging, and epidemiological shifts. Autoregressive integrated moving average (ARIMA) and age-period-cohort (APC) models were also applied, while global health inequalities were evaluated via the Slope Index of Inequality (SII) and Concentration Index (CI).ResultsIncidence and mortality rates were notably higher in individuals under 20 and over 80 years, with males consistently at greater risk than females. Acute Hepatitis A predominates in low-SDI regions, whereas Acute Hepatitis B is more prevalent in high-SDI regions. Projections indicate a continued decline in AVH burden by 2031, driven by population dynamics and epidemiological changes.ConclusionWhile global AVH burden is decreasing, significant disparities persist, warranting tailored interventions to enhance resource equity in high-SDI regions and strengthen healthcare infrastructure in low-SDI areas.